An Analysis upon the Contribution and Effectiveness of Media/Mass Communication to Rural Development in India: Enhancing participation and development in rural India through media and communication (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The mass media like radio and newspapers were of lesser centrality to bring down station in rural society. The electronic media's part in education proposed that radio and television are equipped for rising above the proficiency boundary and could have moved toward becoming media for mass education.In spite of the fact that poverty, starvation and nourishment issues are as yet the real issues in the entire world, lack of concern towards the rural area step by step increments. Subsequently, the rural area is the field that most needs economic, social and cultural help. Notwithstanding, sadly, it is at the highest priority on the rundown of the most dismissed areas.The communication examines completed in the rural areas contribute significantly to the general population in the rural areas to take all the more part in the economic, social and political life, to the issues in the rural areas to be conveyed to the public plan and to the arrangement of information trade and participation amongst individuals and institutions in the rural areas. Information and Communication Technologies (ICTs) can be utilized to help communities in their endeavors for social and economic developments.